Digital pathology in the immunohistochemical evaluation of biomarkers in breast cancer - Lopes, J. (2021)
Currently, the evaluation of biomarkers HER-2 and ER is critical for targeting therapy for breast cancer and is performed by experienced pathologists, which takes time and causes a certain interobserver variability. The use of histological slide scanners coupled with the application of software for immunoexpression quantification can be profitable in pathological laboratories routine. This study aims to compare the quantification of HER-2 and ER immunoexpression employing automatic algorithms, using as standard the evaluation performed by a pathologist.